Risk Difference of Multidrug Resistance Organisms (MDROs) According to Risk Factor and Hand Hygiene Compliance - Kurniawati, Ajeng FS; Satyabakti, Prijono; Arbianti, Novita (Faculty of Public Health, 2015)
ABSTRACTNosocomial infections is still global public health problems. Along with the problems there are resistance bacterial problem to multiple classes of antibiotics, defined as multidrug resistance organisms (MDROs). Incidence rates of MDROs in ICU is higher than in other treatment unit. Rational antibiotic use and controlling the transmission of bacterial is important to avoid MDROs. The purpose of this study was to analyze Risk Differences of MDROs according to risk factors and hand hygiene compliance in ICU patients. This study used case control design with sample size was 20 patients for each case and control groups. Samples in cases group were patients infected by MDROs in ICU, while the samples in control group were patients in ICU didnât infected by MDROs. The independent variable are long term use of antibiotic, length of stay, the use of ventilator, and hand hygiene compliance by health worker. Analyze data used OR (Odds Ratio) and RD (Risk Difference). The conclusion was that Risk Difference of MDROs infection by long term use of antibiotics (OR 10.23 95% CI 1.12 < OR < 93.35; RD = 0.47), length of stay (OR 7.36 95% CI 1.34<OR<40.55; RD = 0.44), the use of ventilator devices (OR 9.00 95% CI 1.64 < OR < 49.45; RD = 0.48) and hand hygiene compliance (OR 6.00 95% CI 1.46 < OR < 24.69; RD = 0.42). The conclusion was that maintaining hygiene before medical treatment, environment and health workers body should be implemented so canât became a media for bacterial MDROs growth.Keywords: antibiotic,ventilator, length of stay, hand hygiene, MDROs